Hybrid Learning: Strategies to Attract Student Learning Interests and Outcomes on Post Pandemic - Ni Wayan Karmini; M. Nurzen S.; Trinandari Prasetyo Nugrahanti; Iwan Ramadhan; Rusliandy Rusliandy; Tekat Sukomardojo (STAI Hubbulwathan Duri, 2023)
The hybrid learning model, also called